Interstitial pneumonia due to Japanese spotted fever - Katsunori Arai; Hirokazu Tokuyasu; Tatsuya Konishi; Toshiyuki Tatsukawa; Kenichi Takeda; Akira Yamasaki (Respirology Case Reports)
Key message We report case of Japanese spotted fever with interstitial pneumonia. In patients with signs of interstitial pneumonia on chest computed tomography, Rickettsial pneumonia should be considered in the differential diagnosis, especially if they have visited a Rickettsia‐endemic area.